Bioinformatics: An Introductory Textbook - Dandekar, Thomas; Kunz, Meik (Springer Berlin Heidelberg, 2023)
This book offers a gripping introduction to the fastest growing field of biology with easy-to-follow examples and a well-prepared appendix for the reader to cook up and experience everything right away. The book gets the reader started with the basics, such as how to easily find sequence information and then analyze it. In further chapters, the authors go into the various analysis options from RNA, DNA and proteins to entire metabolic pathways. Exciting examples from biology are chosen in each chapter to illustrate the analysis. Each chapter concludes with an exercise section that immediately puts what has been learned to use. The subject of this book is a must for any biology student, whether undergraduate or graduate, as bioinformatics is now unearthing amazing insights into the molecular basis of all living things. Computer science students and other students from related sciences will get a good introduction to bioinformatics, as biology and current topics (e.g. AI) are systematically introduced step by step alongside the software. Discover the key to life together with the authors and learn to understand the language of life. This book is a translation of the original German 2nd edition Bioinformatik by Thomas Dandekar and Meik Kunz, published by Springer-Verlag GmbH Germany, part of Springer Nature in 2021. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com). A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation. Springer Nature works continuously to further the development of tools for the production of books and on the related technologies to support the authors.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Bioinformatics; Biomedicine; Computer; Information; Life; Systems Biology